High temperature dielectric properties of ludwigite and its effect on microwave heating process. Issue 3 (3rd July 2019) - Liu, Yajing; Jiang, Tao; Huang, Weijun; Liu, Chenhui; Wang, Junpeng; Xue, Xiangxin
Abstract: To liberate magnetite from ludwigite, the dielectric properties of ludwigite are investigated by cavity perturbation method at 2.45 GHz from 20 to 800 °C. The results show dielectric properties of ludwigite with temperature can be divided into three stages: at the first stage (20–200 °C), the dielectric constant ( ε ′), dielectric loss factor ( ε ″) and loss tangent (tan δ ) increase approximately by 4.55, 47.31 and 38.89%, respectively, at the second stage (200–500 °C), ε ′ increases slowly by 5.19%, while ε ″ and tan δ gradually decrease, at the third stage (500–800 °C), ε ′ first increases rapidly by 6.21% at 500–700 °C and then increases slowly beyond 700 °C, ε ″ and tan δ fluctuate slightly. Meanwhile, the penetration depth ( D p ) decreases significantly at 20–200 °C and decreases slightly at 200–500 °C, but decreases substantially again at 500–700 °C, and finally is closed to the constant value beyond 700 °C. The heating rate of magnetite is faster than those of ascharite and serpentine, which results in the formation of intergranular fractures to promote the liberation of magnetite from ludwigite by microwave heating.